2020
DOI: 10.30605/25409190.179
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Plickers for Formative Assessment of Vocabulary Mastery

Abstract: The use of technology considered has able to help the learning process, especially in teaching English. In the industry revolution 4.0, there are some alternatives to teach English effectively. Plickers is an application that can help the teachers to measure student capability. This application used printable paper clickers to assign each student using the Plickers card. The teacher is instantly checking the student responses and assessment data for every question. This study was using mixed methods design to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Therefore, formative assessment is an ongoing procedure that provides learners with constructive timely feedback, helping them achieve their learning goals and enhancing their achievements (Vogt et al, 2020 ). Formative assessment is a helpful technique that can provide students with formative help by evaluating the interactions between assessment and learning (Chan, 2021 ; Masita & Fitri, 2020 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Therefore, formative assessment is an ongoing procedure that provides learners with constructive timely feedback, helping them achieve their learning goals and enhancing their achievements (Vogt et al, 2020 ). Formative assessment is a helpful technique that can provide students with formative help by evaluating the interactions between assessment and learning (Chan, 2021 ; Masita & Fitri, 2020 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Kent (2019) emphasized that with this application students could perform quick self-evaluations, and teachers could obtain instant assessments as to the topics that the students were good and bad at. Masita and Fitri (2020) found in their study conducted with teachers and students on English teaching that the application could assist formative assessment by providing teachers quickly with student responses and assessment data. They also concluded that it increased student motivation and participation.…”
Section: Discussionmentioning
confidence: 99%
“…Aldır (2014) found in his study conducted on this subject that pre-service teachers did not take the courses related to these contents at a sufficient level during the undergraduate period. In the literature there are studies conducted with secondary school students (Arzfi et al, 2022;Cin Şeker, 2020;Korkmaz et al, 2019;Tuncer & Şimşek, 2019;Yaylak, 2017) and university students (Masita & Fitri, 2020;Mshayisa, 2020;Wood, Brown & Grayson, 2017;Zengin, Bars & Şimşek, 2017) as regards Plickers application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buna ilişkin Aldır (2014) yapmış olduğu çalışmada öğretmen adaylarının lisans döneminde bu içeriklere ilişkin dersleri yeterli görmediklerini tespit etmiştir. Alanyazında Plickers uygulamasına ilişkin ortaokul (Arzfi ve arkadaşları, 2022;Cin Şeker, 2020;Korkmaz ve arkadaşları, 2019;Tuncer & Şimşek, 2019;Yaylak, 2017) ve üniversite öğrencileriyle (Masita & Fitri, 2020;Mshayisa, 2020;Wood, Brown ve Grayson, 2017;Zengin, Bars & Şimşek, 2017) Plickers uygulamasına ilişkin görüş ve tutumlarını belirlemeye yönelik çeşitli çalışmalar gerçekleştirilmiştir. Ancak bu çalışma sosyal bilgiler öğretmen adaylarının kendilerinin bir öğrenci olarak Plickers'ı önce öğrenip (derste) daha sonra derste ve arasınavlarında deneyimlemesinin ardından uygulamayı stajer bir öğretmen olarak (Öğretmenlik Uygulaması I dersi kapsamında) ortaokul öğrencilerine uygulamasını içermesi, hem öğretmen adaylarının uygulamaya ilişkin görüşlerinin hem de ortaokul öğrencileri üzerindeki etkilerine ilişkin gözlemlerine yer verilmesi açısından diğer çalışmalardan ayrılmaktadır.…”
Section: Introductionunclassified